Beyond the embrace: a phenomenological qualitative exploration of the impact of kangaroo mother care (KMC) on couple relationships in China - Xin Ding; Yiyin He; Peizhen Chen; Chunmei He; Jufang Ding; Hongqing Guo; Wenying Yao (BMJ Open)
Objectives To explore the impact of kangaroo mother care (KMC), involving both mothers and fathers, on the dynamics of couple relationships.Design Qualitative phenomenological study.Setting A regional comprehensive centre for child healthcare.Participants 11 couples engaged in KMC with their infants. We created a semistructured interview guide to conduct face-to-face interviews separately with both wives and husbands. The interviews were audio-recorded and transcribed verbatim, and analysed using Braun and Clarke’s thematic analysis technique.Results Analysis of participants’ narratives revealed three pivotal themes: ‘strengthening of couple relationship’, ‘role adaptation and redefinition’ and ‘conflicts and resolution’. These themes collectively illustrated the complex interplay between enhanced emotional intimacy, renegotiated parental roles and the navigation of conflicts within the context of neonatal caregiving.Conclusions KMC may have effects on couple relationships beyond its immediate benefits for the infant. It may potentially influence the emotional and relational dynamics between partners. Couples' experiences with KMC practices are multifaceted and complex. Through the intimate act of KMC, couples may experience a deepening of emotional bonds, redefinition of roles and identities, and encounter both challenges and opportunities for conflict resolution. Adopting a more holistic approach to neonatal care including attention to the couple’s relationship and engaging in KMC is suggested.